Utilization of Melaleuca leucadendron Essential Oil - Rini Pujiarti; Yoshito Ohtani; Titis Budi Widowati; Kasmudjo Kasmudjo (Masyarakat Peneliti Kayu Indonesia, 2011)
The chemical composition, antioxidant, antifungal, and physiological effects of commercial Melaleuca leucadendron LINN. (Kayu Putih) oil from Sukun, East Java, Indonesia was investigated in this study. GC-MS analysis showed the majority compounds of this oil are mixtures of monoterpenes and sesquiterpenes, which 1,8-cineole (53.90%) was the most abundant compound in this oil. In vitro antioxidant assay showed this essential oil possessed antioxidant activity (IC50: 4.24mg/ml). In vitro antifungal assay showed relatively strong antifungal activity of this oil against plant pathogenic fungi of F. oxysporum (IC50: 0.44mg/ml), T. cucumeris (IC50: 0.97mg/ml) and R. oryzae (IC50: 7.71mg/ml). The investigation on the effect of the odor of M. leucadendron oil in this study also showed functional fragrance of this oil for human physiological behavior controlling.